An accurate approximation for the standard normal distribution function. Issue 1 (2nd January 2021) - Eidous, Omar; Abu-Hawwas, Jawaher
Abstract: In this paper, a new approximation for the standard normal cumulative distribution function, Φ( z ) is proposed. The maximum absolute error ( MAE ) of the proposed approximation is 9.37935 × 10 −6 . Comparisons with some existing approximations based on the MAE and mean absolute error (MEAE) are also given. The results show that the proposed approximation is simple and has an acceptable accuracy.